2019
DOI: 10.3390/inorganics7040053
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-2,6-Dicarboxylic Acid Esters (pydicR2) as O,N,O-Pincer Ligands in CuII Complexes

Abstract: The pyridine-2,6-carboxylic esters pydicR2 with R = Me or Ph form the unprecedented mononuclear CuII complexes [Cu(pydicR2)Cl3]− in one-pot reactions starting from pyridine-2,6-carboxychloride pydicCl2, CuII chloride, and NEt3 in MeOH or PhOH solution under non-aqueous conditions. The triethylammonium salts (HNEt3)[Cu(pydicR2)Cl3] were isolated. The methyl derivative could be crystallized to allow a XRD structure determination. Both structures were optimized using DFT calculations in various surroundings rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 65 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Remarkably, we were not able to detect a half-field signal (ΔM S = � 2) which is normally observed for an anti-ferromagnetically coupled system with an S = 0 ground and S = 1 excited state. [30,47,[53][54][55][61][62][63][64][65][66][67][68] In view of the 1.7 % paramagnetic impurity concluded from the magnetic measurements, we assume that the inherently weak and broad spectrum of the dinuclear complex is merged with or even completely covered by the signal of the paramagnetic mononuclear Cu(II) impurity.…”
Section: Magnetic Measurements and Epr Spectroscopymentioning
confidence: 99%
“…Remarkably, we were not able to detect a half-field signal (ΔM S = � 2) which is normally observed for an anti-ferromagnetically coupled system with an S = 0 ground and S = 1 excited state. [30,47,[53][54][55][61][62][63][64][65][66][67][68] In view of the 1.7 % paramagnetic impurity concluded from the magnetic measurements, we assume that the inherently weak and broad spectrum of the dinuclear complex is merged with or even completely covered by the signal of the paramagnetic mononuclear Cu(II) impurity.…”
Section: Magnetic Measurements and Epr Spectroscopymentioning
confidence: 99%
“…Accordingly, many complexes of them have been reported which were designed from various organic ligands especially multi-dentate ligands possessing oxygen and nitrogen donor atoms [8][9][10] such as pyridine-2,6-dicarboxylic acid [10][11][12][13]. The studies have shown that lanthanides complexes can bind with the biomolecular targets and cause alteration in the cellular mechanism of proliferation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the complex in the unit cell is observed in Fig.6. This complex with two triangle plane consist of N(3), O(9), O(11) and N(2), O(5), O(7) and O(1), Ce(1), O(3) atoms are three capped atoms. The sum of bond angles, N(2)-Ce(1)-N(3)=115.32(13), N(1)-Ce(1)-N(2)=122.50(13) and N(1)-Ce(1)-N(3)=122.18(13) equals to 360.00 which indicates that Ce(IV) is located in the center of N(1)N(2)N(3) (x,y, z-1) plane Ce(IV).…”
mentioning
confidence: 99%